Analisis Pengaruh Desain Pekerjaan Dan Budaya Organisasi Terhadap Kinerja SDM Dimediasi Motivasi Kerja - Sholekhati, Nessy Juwita; Irmawati, Irmawati (Politeknik Negeri Padang, 2023)
The aims of this study were to analyze the mediating effect of work motivation on the influence of job design and organizational culture on human resource performance. Research design is a detailed design that is used as a study guide that leads to research objectives. The object of this research is the human resources of the Karanganyar Regency Environmental Service. In this study there was a population of 55 people with a sample of 35 respondents. Sampling used a purposive sampling method, with the criteria of employees who have worked for more than one year and have at least a bachelor's degree. Test validity and reliability using smart PLS analysis on the outer model. Hypothesis testing uses the inner smart PLS model. The results of the analysis analysis show that there is a significant direct effect of work design on human resource performance and work motivation, there is a significant direct effect of organizational culture on work motivation and human resource performance, there is a significant direct effect between work motivation on human resource performance , there is an indirect effect of work design on human resource performance through work motivation mediating variables.